Prevalence of comorbidities in chronic obstructive pulmonary disease patients: A meta-analysis. Issue 19 (May 2017) - Yin, Hong-lei; Yin, Shi-qi; Lin, Qing-yan; Xu, Ying; Xu, Hong-wei; Liu, Tao
Abstract: Background: This study compares the prevalence rates of comorbidities between chronic obstructive pulmonary disease (COPD) and non-COPD control patients reported in literature. Method: Literature was searched in several electronic databases. After the selection of studies by following précised eligibility criteria, meta-analyses of odds ratios (ORs) were carried out with subgroup and sensitivity analyses under random effects model. Results: Eleven studies (47, 695, 183 COPD and 47, 924, 876 non-COPD control patients' data) were used for meta-analysis. Average age of COPD patients was 66.66 ± 8.72 years of whom 55.4 ± 11.9% were males. The prevalence of cardiovascular comorbidities [OR 1.90, 95% confidence interval (95% CI) 1.59–2.28; P  < .00001], cerebrovascular comorbidities (OR 1.84, 95% CI 1.47–2.31; P  < .00001), hypertension (OR 1.45, 95% CI 1.31–1.61; P  < .00001), diabetes mellitus (OR 1.22, 95% CI 1.07–1.38; P  = .003), neurological and psychiatric disorders (OR 1.78, 95% CI 1.48–2.14; P  < .00001), gut and renal disorders (OR 1.96, 95% CI 1.43–2.68; P  < .00001), musculoskeletal disorders (OR 1.51, 95% CI 1.27–1.78; P  < .00001), non-COPD respiratory comorbidities (OR 2.81, 95% CI 2.52–3.14; P  < .00001), and cancer (OR 1.67, 95% CI 1.25–2.23; P  = .0005) were significantly higher in COPD patients than in non-COPD controls. Conclusion: COPD is associated with significantly higher comorbidities than in other diseases that should be taken into consideration in COPD control strategies. Abstract : Supplemental Digital Content is available in the text